2019
DOI: 10.1007/s00421-018-04058-6
|View full text |Cite
|
Sign up to set email alerts
|

Montmorency cherry supplementation improves 15-km cycling time-trial performance

Abstract: Aim Montmorency cherries are rich in polyphenols that possess antioxidant, anti-inflammatory and vasoactive properties. We investigated whether 7-day Montmorency cherry powder supplementation improved cycling time-trial (TT) performance. Methods 8 trained male cyclists ( : 62.3 ± 10.1 ml kg −1 min −1 ) completed 10-min steady-state (SS) cycling at ~ 65% followed by a 15-km TT on two occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 57 publications
1
57
1
2
Order By: Relevance
“…Previous studies showed improved TT performance by 2.4% and 4.6% after consuming 300 mg of NZBC extract and~258 mg anthocyanins from MC for 7 days compared to PLA [6,43]. The 600 mg of NZBC extract provided~210 mg•day −1 of anthocyanins, which is similar to the amount in Morgan et al [43], however, the anthocyanin source used in that study also provided a total of 458.2 mg•day −1 of polyphenols, potentially influencing the performance outcome. Nevertheless, the length of the study might justify the lack of significance showed on this occasion.…”
Section: 1 Km Ttmentioning
confidence: 94%
“…Previous studies showed improved TT performance by 2.4% and 4.6% after consuming 300 mg of NZBC extract and~258 mg anthocyanins from MC for 7 days compared to PLA [6,43]. The 600 mg of NZBC extract provided~210 mg•day −1 of anthocyanins, which is similar to the amount in Morgan et al [43], however, the anthocyanin source used in that study also provided a total of 458.2 mg•day −1 of polyphenols, potentially influencing the performance outcome. Nevertheless, the length of the study might justify the lack of significance showed on this occasion.…”
Section: 1 Km Ttmentioning
confidence: 94%
“…Sofern die gleiche Referenzsubstanz ("Standard") zur Quantifizierung verwendet wurde, können die Werte aus der gleichen Methode miteinander verglichen werden. Diese Voraussetzung ist in den hier berücksichtigten Studien gegeben, da Cyanidin-3-O-Glucosid als Referenzsubstanz benutzt wurde (außer in [35]), soweit überhaupt angegeben (keine Angabe zur Referenzsubstanz in [3], [4], [6], [21], [26], [28], [29], [31], [33]).…”
Section: Methodikunclassified
“…Zum gegenwärtigen Zeitpunkt ist die Evidenz der Wirksamkeit der Montmorency-Produkte bei sportlicher Belastung als "mäßig" einzustufen, denn die 4 Studien mit dem konfirmatorischen Design hatten unterschiedliche Zielparameter: Sprungkraft, Muskelschmerz und Wohlbefinden (nicht besser als Placebo [1]), Muskelfunktion, -schmerz und Marker (Entzündung, Muskelschädigung) etc. (besser als Placebo im Zielkriterium Muskelfunktion [7]), Radfahrzeit, Muskeloxygenierung, pulmonaler Gasaustausch, kapilläres Lactat (besser als Placebo in allen Zielkriterien [33]) und Parameter unter Belastung (PuB) am Ellenbogen und Schmerzen im Alltag (besser als Placebo in allen Zielkriterien [10]).…”
Section: Methodikunclassified
“…5), and these results may suggest that oxygen utility capacity improved following BE intake at baseline and during exercise, further supporting other recent findings regarding anthocyanin intake and skeletal muscle oxygen utility capacity. Morgan et al demonstrated increases in baseline StO 2 following anthocyanin intake (66) . Notably, in addition to a significant difference in StO 2 at baseline, we also found significantly higher StO 2 during leg extension exercise.…”
Section: Oxygen Utility Capacitymentioning
confidence: 99%
“…Notably, in addition to a significant difference in StO 2 at baseline, we also found significantly higher StO 2 during leg extension exercise. However, it is important to note that our study incorporated single leg extension exercise, while Morgan et al investigated oxygen utility capacity with cycling exercise (66) . Therefore, it may be of interest to investigate oxygen utility capacity during exercise requiring greater muscle recruitment (e.g.…”
Section: Oxygen Utility Capacitymentioning
confidence: 99%